Pemanfaatan Ekstrak Etanol Daun Gulinggang (Cassia alata Linn) sebagai Bahan Antijamur pada Produk Sabun Mandi (Utilization of Ethanol Extract of Gulinggang (Cassia alata Linn) Leaves as Antifungal in Body Soap Bar) - Nurmilatina, Nurmilatina; Prabawa, I Dewa Gede Putra (Kementerian Perindustrian, 2017)
Gulinggang (Cassia alata Linn) leaves extract has secondary metabolite compounds such as alkaloids, saponins, tannins, phenolic, triterpenoids, quercetin and steroids. These compounds are very useful, for example as an antifungal substances. The objective of this study is to utilize gulinggang leaves extract to produce antifungal bath soap. Gulinggang leaves were extracted by maceration method using ethanol solvent ratio 1:4 for 3 days. This extract was applied to the soap base formula using variations 0%, 5%, 10% and 20%. The organoleptic parameters of the body soap bar, such as aroma, texture, color, total panelist acceptance, and also the pH were tested. The inhibitory test was performed using Candida albicans fungus. The results showed that 5% of gulinggang leaves extract on soap gave the best result with organoleptic value 3.70; pH 9.76 and the mean diameter of the fungal resistance was 15.00 mm.Keywords: antifungal, Candida albicans, Cassia alata Linn, extraction, ethanol